2019
DOI: 10.1039/c9lc00927b
|View full text |Cite
|
Sign up to set email alerts
|

Controllable cell manipulation in a microfluidic pipette-tip design using capacitive coupling of electric fields

Abstract: Capacitive coupling of electric fields diminishes energy dissipation and offers superior control over field parameters, resulting in predictable biological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…TiO 2 has also been proposed as a suitable dielectric material for titanium electrodes. ,, This layer limits the passage of off-target currents through the electrolyte solution. Wimberger et al found that passivated electrodes led to more consistent cell inactivation at different electric field strengths than exposed electrodes because stochastic electrolysis effects were minimized (Figure A) . 18 μm thin layers of PDMS have also been used as a passivating layer for interdigitated electrodes .…”
Section: Technological Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…TiO 2 has also been proposed as a suitable dielectric material for titanium electrodes. ,, This layer limits the passage of off-target currents through the electrolyte solution. Wimberger et al found that passivated electrodes led to more consistent cell inactivation at different electric field strengths than exposed electrodes because stochastic electrolysis effects were minimized (Figure A) . 18 μm thin layers of PDMS have also been used as a passivating layer for interdigitated electrodes .…”
Section: Technological Improvementsmentioning
confidence: 99%
“…Passivation decreases the variation in lysis efficiency across all buffer types. Reproduced with permission from ref . Copyright 2019 Royal Society of Chemistry.…”
Section: Technological Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boukany et al utilized a micro-nano-micro-channel for the precise delivery of transfection agents to the trapped single cells [ 27 ]. In single-cell electroporation systems, complicated micro/nano-fluidic channels [ 26 , 27 , 28 , 29 ] or single-cell micromanipulation units [ 30 , 31 , 32 , 33 ] were usually required. In addition, most of these systems were combined with an optical detection tool for visualizing electroporation results [ 34 ].…”
Section: Introductionmentioning
confidence: 99%